ChemInform Abstract: Csp3—Csp3 Homocoupling Reaction of Benzyl Halides Catalyzed by Rhodium. Issue 2 (January 2015) - Sato, Kazuyuki; Inoue, Yuichi; Mori, Tomohisa; Sakaue, Atsushi; Tarui, Atsushi; Omote, Masaaki; Kumadaki, Itsumaro; Ando, Akira
Abstract The Rh‐catalyzed homocoupling of benzyl bromides under mild reaction conditions is established.